1988
DOI: 10.1093/chemse/13.2.295
|View full text |Cite
|
Sign up to set email alerts
|

A multidimensional statistical study of similarities between 74 notes used in perfumery

Abstract: Abstract. From a data bank of 2467 odoriferous products, the similarities between 74 notes used in perfumery were calculated. The similarity matrix (74,74) contains -63% of zero values and shows that only a few pairs of notes present high similarity coefficients. A fine analysis using ascending hierarchical taxonomy with the complete linkage procedure shows that 14 notes are isolated while 60 notes are regrouped in 27 groups containing two to four notes. The isolated notes correspond to well-defined structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
111
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(120 citation statements)
references
References 0 publications
9
111
0
Order By: Relevance
“…These similarities, which are well known in perfumery (Chastrette et al, 1988(Chastrette et al, , 1991, are reflected in the loading plots shown in Fig. 1 because pairs of attributes strongly associated appear close to each other.…”
Section: Figure 1 Near Here]supporting
confidence: 58%
See 2 more Smart Citations
“…These similarities, which are well known in perfumery (Chastrette et al, 1988(Chastrette et al, , 1991, are reflected in the loading plots shown in Fig. 1 because pairs of attributes strongly associated appear close to each other.…”
Section: Figure 1 Near Here]supporting
confidence: 58%
“…Regarding descriptors influencing PC2, a coefficient of 0.7 was used for 'green', 0.8 for 'vegetable' and 0.6 for 'leafy'. In the case of 'minty' and 'camphoraceous', which are also similar odors (Chastrette et al, 1988), the coefficient was 0.6. For the rest of related descriptors, values were: 0.9 ('musky', 'animal', 'balsamic', 'vanilla', 'woody', 'medicinal', and 'rosy'), 0.8 ('floral', 'hyacinth', 'oily', 'waxy', 'fatty', and 'honey') and 0.7 ('gassy').…”
Section: Figure 1 Near Here]mentioning
confidence: 95%
See 1 more Smart Citation
“…In the case of a sorting task, we can suppose that identification helps participants to find some lexical criterion to form their groups. In agreement with this hypothesis, Chastrette, , & Sauvegrain (1988) argued that odors are more often sorted on the basis of their common taxonomic origin rather than on the basis of similarities in odor quality. This hypothesis could be confirmed also by this unexpected finding, our French participants separated fruit from flowers odorants very clearly compared to the two other groups of participants whereas it was the opposite trend that emerged from the MDS in the first sorting task.…”
Section: Discussionmentioning
confidence: 90%
“…Besides specialized categorization systems, such as the wine aroma wheel (Noble et al, 1984), the beer flavor wheel (Meilgaard, 1982), or Carl Linnaeus' for medical plants (Linneus, 1752), different categorizations have been proposed for natural odors (e.g. Zarzo and Stanton, 2006;Mamlouk and Martinetz, 2004;Chastrette et al, 1988;Abe et al, 1990;Crocker and Henderson, 1927;Henning, 1916).…”
Section: Perceptionmentioning
confidence: 99%